2016
DOI: 10.1016/j.chiabu.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma and neighborhood-level crime interact in predicting adult posttraumatic stress and major depression symptoms

Abstract: Previous research has identified several individual-level factors that modify the risk of childhood trauma on adult psychiatric symptoms, including symptoms of major depression (MD) and posttraumatic stress (PTS). Neighborhood-level factors also influence the impact of individual-level exposures on adult psychopathology. However, no prior studies to our knowledge have explored cross-level interactions between childhood trauma and neighborhood-level factors on MD and PTS symptoms. The purpose of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 38 publications
5
25
1
1
Order By: Relevance
“…Attachment adversity often co‐occurs with other forms of interpersonal victimization (Bailey, Moran, & Pederson, ; D. Grasso, Dierkhising, Branson, Ford, & Lee, ; McKelvey et al., ; Seto, Babchishin, Pullman, & McPhail, ; Thoresen, Myhre, Wentzel‐Larsen, Aakvaag, & Hjemdal, ). Our findings are consistent with research suggesting that the combination of interpersonal trauma and attachment adversity has an adverse synergistic effect on psychosocial development (Lowe et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…Attachment adversity often co‐occurs with other forms of interpersonal victimization (Bailey, Moran, & Pederson, ; D. Grasso, Dierkhising, Branson, Ford, & Lee, ; McKelvey et al., ; Seto, Babchishin, Pullman, & McPhail, ; Thoresen, Myhre, Wentzel‐Larsen, Aakvaag, & Hjemdal, ). Our findings are consistent with research suggesting that the combination of interpersonal trauma and attachment adversity has an adverse synergistic effect on psychosocial development (Lowe et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with those of a meta-analysis that compared rates of childhood trauma across countries and found that that Lower and Middle Income Countries (LMIC) had higher rates than upper income countries [29]. Notably, LMICs have higher rates of crime, poverty and unemployment—all of which are socio-economic factors known to influence childhood trauma rates [3031]. Alternatively, the high rates of reported childhood trauma in our sample may relate to measurement with the CTQ.…”
Section: Discussionsupporting
confidence: 89%
“…Cotidianamente en las calles ocurren asaltos y violencia en diferentes modalidades como cogoteo, arrebatos, trepar casas o "sarakeo" (robo de celulares desde el bolsillo con los dedos de las manos) (27)(28)(29). También es común la violencia de las barras bravas y pandillas, las mismas que asaltan a los transeúntes o se atacan mutuamente en las denominadas "guerreadas": enfrentamientos callejeros entre grupos disociales que se disputan territorios, mujeres o por venganza (30).…”
Section: Inseguridad Ciudadanaunclassified